Edukasi Perilaku Pola Hidup Sehat Dengan Penanaman Apotek Hidup - Hefriady Hefriady; Trecy Austin (Jurnal Pengabdian Masyarakat (abdira), 2022)
Community Service is an effective and educative media with the process of fielding several students in the midst of the community to capture and appreciate the activities of community life during the Covid 19 Pandemic. In addition, students are also able to capture the problems faced by the community, the resources to be developed and aspirations and hopes of the community. Community Service takes the theme of the climate village program because currently we are still hit by the Covid 19 pandemic. The objectives of Community Empowerment are, First, the community can live a healthy lifestyle, Second, the community can practice planting live pharmacies to meet kitchen needs and increase body immunity. The method applied is Forum Group Discussion, Socialization, Education, Direct Practical Assistance. The community is given independence independently as a result of short-term Community Empowerment activities. It can be concluded that this activity provides short-term and long-term benefits. The community coordinates with each other to carry out community service and jointly maintain the preservation and cleanliness of the environment with plants in front of the house.